The Prospect of Better Utilization of The Potential Productivity of the Soil to Increasing Rice Yields in Indonesia - Tedjojuwono Hadiprawiro (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 1969)
-